2005
DOI: 10.1074/jbc.m405204200
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-12-induced Interferon-γ Production by Human Peripheral Blood T Cells Is Regulated by Mammalian Target of Rapamycin (mTOR)

Abstract: Depending on the type of external signals, T cells can initiate multiple intracellular signaling pathways that can be broadly classified into two groups based on their sensitivity to the immunosuppressive drug cyclosporin A (CsA). Interleukin (IL)-12-mediated interferon (IFN)-␥ production by activated T cells has been shown to be CsA-insensitive. In this report, we demonstrate that the IL-12-induced CsA-resistant pathway of IFN-␥ production is sensitive to rapamycin. Rapamycin treatment resulted in the aberran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 38 publications
6
35
0
1
Order By: Relevance
“…Previous studies indicate that rapamycin-mediated inhibition of mTOR signaling results in reduced IL-12-induced IFN-g production in human T cells (38). In contrast, we see increased production of IFN-g in recall responses when our combination regimen is administered during immunization; however, we have not extensively explored the effects of combining CTLA-4 blockade with rapamycin on early cytokine cues during CD8 + T cell priming.…”
Section: Cd8mentioning
confidence: 75%
“…Previous studies indicate that rapamycin-mediated inhibition of mTOR signaling results in reduced IL-12-induced IFN-g production in human T cells (38). In contrast, we see increased production of IFN-g in recall responses when our combination regimen is administered during immunization; however, we have not extensively explored the effects of combining CTLA-4 blockade with rapamycin on early cytokine cues during CD8 + T cell priming.…”
Section: Cd8mentioning
confidence: 75%
“…Results are shown for the first 30 d after the first islet infusion and after the second islet infusion in patients who received 2 or more infusions (n = 11). *P < 0.05, # P < 0. tions were significantly elevated (30,52, and 57 ng/ml; P = 0.007 versus nondiabetic control; data not shown).…”
Section: Figurementioning
confidence: 83%
“…61 IL-12/IL-18 -induced synthesis of IFN-␥ by human peripheral T cells is also inhibited by sirolimus. 134 We have demonstrated that IL-12/IL-18 -dependent IFN-␥ secretion from human coronary artery-infiltrating T cells is prevented by a p38 MAPK inhibitor, is partially diminished by sirolimus, and is not affected by cyclosporine or the 3-hydroxyl-3-methylglutaryl coenzyme A reductase inhibitor atorvastatin. 63 In contrast, cyclosporine, but not p38 MAPK inhibition, decreased IFN-␥ synthesis secondary to T-cell polyclonal activation in this organ culture system.…”
Section: Effects Of Therapeutic Agents On Ifn-␥ Productionmentioning
confidence: 84%